CARBON STOCK AND REMOVAL OF CO2 IN YOUNG STANDS OF FOREST RESTORING IN RONDÔNIA - Queiroz, Alexandre; Sanquetta, Mateus Niroh Inoue; Bastos, Alexis; Sanquetta, Carlos Roberto; Corte, Ana Paula Dalla (Floresta, 2019)
This study aims to quantify the carbon stock in young stands of forest restoration planted with native species on family farms in the north of the state of Rondônia. A forest inventory of the stands was carried out in 20 permanent plots. Biomasses of 20 sample trees located near each sample plot were determined by the destructive method. Laboratory analyses of carbon content in plant tissues were made on samples brought from the field. Biomass partitioning by compartments was evaluated and regression equations were applied for estimation from dendrometric inventory data. The total dry biomass was distributed as follows: 52% in shafts, 22% in branches, 13% in foliage and 13% in roots. The calculated carbon stock in the stands was 15.7 t.ha-1 at 75 months of age, which corresponds to an average annual carbon fixation of 2.5 t.ha-1.year-1. Such values represent a removal of carbon dioxide from the atmosphere of 57.6 tCO2eq.ha-1 and 9.2 tCO2eq.ha-1.year-1. It was concluded that, in spite of being young, the stands have an expressive stock of carbon, which corresponds to about 8.3% of what is stored in the Amazonian native forest.